Podbevšek in Cvelbar - Dović, Marijan (Slavistična revija, 2002)
In this article I explore unverified, yet stubborn rumours about Podbevšek's plagiarism. I combine traditional comparative analysis with some of the accessible empirical tests and combining the two approaches manage to refute them pretty reliably. I also outline some of the more general aspects of authorship analysis.
Keywords: Cvelbar, Jože, 1895-1916; history of literature; literarna zgodovina; plagiati; Podbevšek, Anton, 1898-1981; Slovene literature; slovenska književnost; slovenska poezija